Návrh rozvoje produktového portfolia společnosti působící v papírenském průmyslu - Krutišová, Zuzana (Vysoké učení technické v Brně. Fakulta podnikatelská, 2021)
Diplomová práce se zabývá tématem strategického řízení rozvoje podniku se situačním zhodnocením v oblasti možností rozšíření produktového portfolia a následným návrhem klíčových kroků pro vstup na trh s novým produktem. V teoretické části práce je popsána problematika strategického a investičního rozhodování o produktové strategii a rozvoje produktu včetně popisu vybraných analyticko-evaluačních metod. Analytická část práce se zaměřuje na aplikaci vybraných metod ve vybraném kontextu podnikového prostředí za účelem identifikace klíčových faktorů a zhodnocení možností pro rozhodování s ohledem na novou produktovou strategii. Návrhová část vypracovává zvolenou variantu rozvoje produktové strategie s investičním posouzením rozšíření nové produktové řady včetně doporučení obchodnímu oddělení firmy.

The diploma thesis deals with the topic of strategic management of the company's development with situational evaluation in the area of possibilities of expanding the product portfolio and subsequent proposal of key steps for entering the market with a new product. The theoretical part of the thesis describes the issues of strategic and investment decision-making on product strategy and product development, including a description of selected analytical and evaluation methods. The analytical part of the work focuses on the application of selected methods in a selected context of the business environment in order to identify key factors and evaluate the possibilities for decision-making with respect to the new product strategy. The final part develops the selected variant of product strategy development with an investment assessment of the expansion of a new product line, including recommendations to the company's sales department.
The Proposal for the Development of the Product Portfolio of a Company Operating in the Paper Industry
Keywords: produktová strategie; produktové portfolio; investice; SWOT analýza; projektové riziko; product strategy; product portfolio; investments; SWOT analysis; project risk